Functional Basis of Asymmetrical Lower-Body Skeletal Morphology in Professional Australian Rules Footballers. Issue 3 (March 2020) - Hart, Nicolas H.; Newton, Robert U.; Weber, Jason; Spiteri, Tania; Rantalainen, Timo; Dobbin, Michael; Chivers, Paola; Nimphius, Sophia
Abstract : Abstract: Hart, NH, Newton, RU, Weber, J, Spiteri, T, Rantalainen, T, Dobbin, M, Chivers, P, and Nimphius, S. Functional basis of asymmetrical lower-body skeletal morphology in elite Australian footballers. J Strength Cond Res 34(3): 791–799, 2020—Bone strength is a product of its material and structural properties and is highly responsive to mechanical load. Given the measureable and adaptable features of bone, and thus relevance to medical screening, injury prevention, and injury management in athletes, this study describes the lower-body skeletal morphology of professional Australian rules footballers. Using a cross-sectional and quantitative study design, 54 professional Australian rules football players ( n = 54; age: 22.4 ± 3.8 years; height: 189.0 ± 7.5 cm; body mass: 86.0 ± 8.6 kg; tibial length: 436.1 ± 29.2 mm; and body fat: 9.9 ± 1.7%) underwent tibiofibular peripheral quantitative computed tomography scans for the kicking and support limbs, and a whole-body dual-energy X-ray absorptiometry scans. The support leg was significantly stronger than the kicking leg (bone strength: p ⩽ 0.001; d = 0.47) with significantly greater bone mass ( p < 0.001; d = 0.28), cross-sectional areas ( p ⩽ 0.002; d = 0.20), and greater cortex thickness ( p = 0.017; d = 0.20), owing to significantly greater periosteal apposition ( p ⩽ 0.001; d = 0.29) and endocortical expansion ( p = 0.019; d = 0.13), despite significantly lower cortical density ( p = 0.002; d = −0.25). Disparate skeletal morphology between limbs highlights context-specific adaptive responses to mechanical loads experienced during game-based tasks. Practitioners should concomitantly measure material and structural properties of musculoskeletal tissue when examining fragility or resilience to better inform medical screening, monitoring, and injury risk stratification. Support leg axial loading highlights a potential avenue for interventions aiming to remediate or optimize bone cross-sectional area.